Three‐Dimensional MXenes for Supercapacitors: A Review. Issue 4 (2nd March 2022) - Li, Kangle; Li, Jiapeng; Zhu, Qizhen; Xu, Bin
Abstract: Supercapacitors have the characteristics of high power density and long cycle life, but the low energy density limits their further development. The 2D transitional metal carbides/nitrides (MXenes) show great application prospects in the field of supercapacitors due to their superior volumetric capacitance, metallic‐like conductivity, tunable surface terminations, and structural advantages. However, like other 2D materials, MXenes suffer from the inevitable problem of nanosheet restacking and aggregation, which reduces the overall active surface sites and blocks the accessibility of the electrolyte ions. The transformation of 2D MXene nanosheets into 3D architectures is proven effective to overcome the restacking problem. The review briefly summarizes the preparation strategies of 3D MXene materials, including template‐assisted method, framework‐assisted method, chemical assembly method, foaming method, and other methods with the discussion centered on the performances of 3D MXenes in supercapacitors. Finally, an outlook on the current progress and opportunities is given to highlight the increasing popularity of 3D MXenes in supercapacitors. Abstract : 3D MXene materials show promising potential for high‐performance supercapacitors. The review summarizes the advantages and the recent progress of 3D MXenes for supercapacitors. The preparation strategies, including template‐assisted method, framework‐assisted method, chemical assembly method, foaming method, and other methods, together with the capacitive performance are systematically demonstrated. The challenges and perspectives of 3D MXenes for supercapacitors are also discussed.